The human factor in law enforcement an exploratory study of the attitudes of policemen toward prostitution. [article].
The attitudes of law enforcers toward the person of the prostitute and the act of prostitution were examined using the multiple case study and survey method. Twenty-five policemen were interviewed in depth while one hundred eighty-three participated in the survey. Results revealed a high level of knowledge of the law among the respondents. However, their feelings and behavioral inclinations did not support their knowledge of the law. To a limited extent -, the variables 'rank' and number of years in Metro Manila' accounted for some of the variations in the cognitive and affective component of the attitude, respectively. Personal encounters with prostitutes, actual experiences in enforcing the law against prostitution, and some sociocultural factors helped shaped these attitudes.